Membrane properties modulation by SanA: implications for xenobiotic resistance in Salmonella Typhimurium - Aleksandrowicz, Adrianna; Kolenda, Rafał; Baraniewicz, Karolina; Thurston, Teresa L. M.; Suchański, Jarosław; Grzymajlo, Krzysztof (Frontiers in Microbiology, 2024)
Introduction Multidrug resistance in bacteria is a pressing concern, particularly among clinical isolates. Gram-negative bacteria like Salmonella employ various strategies, such as altering membrane properties, to resist treatment. Their two-membrane structure affects susceptibility to antibiotics, whereas specific proteins and the peptidoglycan layer maintain envelope integrity. Disruptions can compromise stability and resistance profile toward xenobiotics. In this study, we investigated the unexplored protein SanA’s role in modifying bacterial membranes, impacting antibiotic resistance, and intracellular replication within host cells. Methods We generated a sanA deletion mutant and complemented it in trans to assess its biological function. High-throughput phenotypic profiling with Biolog Phenotype microarrays was conducted using 240 xenobiotics. Membrane properties and permeability were analyzed via cytochrome c binding, hexadecane adhesion, nile red, and ethidium bromide uptake assays, respectively. For intracellular replication analysis, primary bone marrow macrophages served as a host cells model. Results Our findings demonstrated that the absence of sanA increased membrane permeability, hydrophilicity, and positive charge, resulting in enhanced resistance to certain antibiotics that target peptidoglycan synthesis. Furthermore, the sanA deletion mutant demonstrated enhanced replication rates within primary macrophages, highlighting its ability to evade the bactericidal effects of the immune system. Taking together, we provide valuable insights into a poorly known SanA protein, highlighting the complex interplay among bacterial genetics, membrane physiology, and antibiotic resistance, underscoring its significance in understanding Salmonella pathogenicity.